ADAPTASI ALAT UKUR DATING ANXIETY SCALE FOR ADOLESCENTS (DAS-A) VERSI BAHASA INDONESIA - Iin, Hurun; Kartini, Kartini; Viella, Ovella Livta; Vlarisa, Vlarisa; Wyandini, Diah Zaleha; Hidayat, Ghinaya Ummul Mukminin (JURNAL KELUARGA SEHAT SEJAHTERA, 2024)
Dating anxiety is a phenomenon commonly experienced during dating. Although much research has been conducted on dating anxiety measurement tools abroad, the adaptation of these tools in Indonesian cultural context remains limited. Therefore, this study aims to examine the reliability and validity of the Dating Anxiety Scale for Adolescents adapted in Indonesia. The measurement scale consists of 21 items assessing 3 dimensions namely Fear of Negative Evaluation, Social Distress-Dating, and Social Distress-Group. The study involved 202 respondents aged 18-30 years in Indonesia. The results of confirmatory factor analysis indicated that the model did not fully fit the data, such as chi-square value of 531.790, CFI 0.770, TLI 0.739, and NFI 0.701, which did not meet the standard fit criteria. However, the reliability test results with Cronbach’s Alpha coefficient showed a significant value of 0.909, indicating this measurement tool has good internal consistency and can be relied upon to measure dating anxiety.